1999
DOI: 10.1046/j.1365-2141.1999.01732.x
|View full text |Cite
|
Sign up to set email alerts
|

The genetic variability of the VH genes in follicular lymphoma: the impact of the hypermutation mechanism

Abstract: Summary. Follicular lymphoma (FL) cells have inherited an activated hypermutation mechanism from their origin of germinal centre B cells. Based on today's knowledge of the intrinsic properties related to this mechanism and the V H base composition, reconsideration of previous reports should be made on a broader range of samples. The present study examined the mutation pattern of the V H genes expressed by 55 cases of FL. FL V H genes showed evidence of antigenic selection in 30% of cases with 88% carrying a fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
28
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 79 publications
5
28
0
1
Order By: Relevance
“…19 Tsuiji et al 20 reported IgM þ memory B cells more frequently express VH3 family genes than do naive B cells. Noppe et al 21 reported VH usage in nodal follicular lymphoma cases as VH3 70%, VH4 19% and VH1 11%; Bahler et al 22 reported it as VH3 67%, VH4 22% and VH1 8%. From their data, duodenal follicular lymphomas of our series showed a higher usage of VH4 and VH5 than did nodal cases.…”
Section: Duodenal Follicular Lymphomamentioning
confidence: 99%
“…19 Tsuiji et al 20 reported IgM þ memory B cells more frequently express VH3 family genes than do naive B cells. Noppe et al 21 reported VH usage in nodal follicular lymphoma cases as VH3 70%, VH4 19% and VH1 11%; Bahler et al 22 reported it as VH3 67%, VH4 22% and VH1 8%. From their data, duodenal follicular lymphomas of our series showed a higher usage of VH4 and VH5 than did nodal cases.…”
Section: Duodenal Follicular Lymphomamentioning
confidence: 99%
“…No sites were found in FR2 in either V H or V L in keeping with the internal location of this region in the antibody protein. To broaden the analysis, the location of sites in the published V H genes of an additional 69 FL 5,6,8 were analysed (Figure 2b). The focusing of V H sites within CDR2 and CDR3 (41 and 29% of sites, respectively) was confirmed.…”
Section: Letters To the Editormentioning
confidence: 99%
“…In all, 18% of sites were created through an essential aa replacement at both positions 1 and 3 of the motif, but only in a minority (9%) by an essential aa replacement at position 3 alone. A more detailed analysis of the generation of N-glycosylation sites in the V H CDR2 was performed and included sequences from cited references 5,6,8 (Table 2). All 47 sequences with CDR2 motifs used V H 3 (n ¼ 35) and V H 4 (n ¼ 12) genes.…”
Section: Letters To the Editormentioning
confidence: 99%
See 2 more Smart Citations